Numerical analysis of dump slope stability using material properties obtained by parallel gradation method - Rudra E.S.C.K.; Gadepaka P.R.; Rai R.; Jaiswal A. (My University, 2025)
The stability of the dump slope depends on many parameters, mainly the shear strength of the dump material. Obtaining strength parameters of dump material is vital in dump stability analysis. Dump material consisting of particles of varying sizes, as large as 1000 mm, is typical. It is challenging to obtain the material strength properties of such large particles in the laboratory. Extrapolation of the material strength properties of the modelled samples prepared by parallel gradation technique is used to calculate the dump material strength properties in this study. A closer agreement is found between the predicted and calculated values of the angle of internal friction. Numerical modelling has been carried out with the obtained material properties using RS2 V9.0, a finite element package, to analyse the stability of a dump slope. It is observed from the results that FOS (factor of safety) increase with an increase in dmax (maximum particle size), keeping the shape of the PSD (particle size distribution) curve constant. The paper develops a slope stability analysis methodology considering particle size's effect on slope stability. The proposed method can be used for accuracy and reliable results for slope stability analysis. © The Author(s) 2024.